Can Numeration Ability Be Enhanced Through Physical Activity of Traditional Tabak Games? (Department of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this study was to develop traditional tabak games into playing and learning media for elementary school students’ Mathematics learning. The research method used is a product development activity, so this type of research includes research and development. In the R&D research model chosen, the research and development model developed by (Gall Borg & P). Based on the stages of the research that has been carried out, the results of this research are a discovery in learning physical education and learning mathematics based on culture which is packaged in traditional Tabak games, and the advantages of this research result are made in video form and can be accessed easily via YouTube account. The conclusion in this study is that the traditional game of tabak based on numeracy skills is a discovery in learning mathematics and physical education based on culture which is packaged through tabak games. This research innovation makes it easier for elementary school students to understand mathematics learning, especially arithmetic material, and can be applied through physical education learning and students can play independently and in groups in the student’s neighborhood. This product can help to enrich the cultural knowledge of West Kalimantan and increase physical activity.